OPTIMIZATION AND CHARACTERIZATION OF SNAIL MUCUS (Achatina fulica) PEEL-OFF GEL USING FACTORIAL DESIGN METHOD - Ramadhani, Dwi Asih; Winanta, Aji; Putra Taufan, Indra (Jurnal Farmasi Sains dan Praktis, 2026)
Indonesia, a tropical country characterized by year-round sun exposure, faces increasing demand for innovative cosmetic formulations with stable and acceptable physicochemical properties. This study aimed to optimize the formulation of a snail mucus peel-off gel mask using a 2² factorial design approach. A peel-off gel snail mask containing 9% snail mucus combined with polyvinyl alcohol (PVA) and sodium carboxymethyl cellulose (CMC-Na) as gelling agents was developed and evaluated. The physical properties of the peel-off gel snail mask were evaluated through organoleptic observations, stickiness tests, spread ability assessments, drying speed measurements, viscosity analysis and pH determination. Subsequently, contour plots were generated and superimposed to delineate the feasible formulation region. Two formulations located within the feasible region were identified: F1 (4.25% CMC-Na and 14.89% PVA) and F2 (4.5% CMC-Na and 14.61% PVA). Rather than representing a single absolute optimum, these formulations exhibited different performance characteristics within the defined optimization constraints. Further investigation into the gelling agents indicated that CMC-Na significantly influenced stickiness and spread ability, while PVA primarily affected viscosity. Drying speed was influenced by the interaction between both polymers.  The factorial design approach successfully defined a formulation space that satisfies predefined physicochemical criteria for peel-off gel masks, providing a rational basis for further formulation refinement.